Purulent-inflammatory manifestations in the oropharynx in children with infectious mononucleosis - L. N. Tuychiev; N. U. Tadjieva; G. T. Shermukhamedova; Sh. A. Tashpulatova (LLC "Diagnostics and Vaccines", 2024)
The results of a prospective study of patients with infectious mononucleosis (MI) hospitalized in City hospital of infectious diseases No. 1 are presented. The aim of the research was to study the etiology of the purulent-inflammatory process in the oropharynx in MI, as well as to identify some risk factors leading to its development. Мaterials and methods. All 120 patients under the age of 18 years were analyzed with clinical and laboratory parameters, as well as bacteriological examination of a smear from the mucous membranes of the tonsils. Results. In the examined patients, symptoms of intoxication, an increase in body temperature ≥ 38°C, headaches, enlargement and soreness of all groups of lymph nodes, sore throat when swallowing, difficulty breathing through the nose were revealed in 100% of cases. Changes in the tonsils in all patients had inflammatory changes in the mucous membranes, hyperemia and hypertrophy of the palatine tonsils with purulent or curdled plaque of gray-yellow color (48.3%), and in other cases, catarrhal manifestations in the form of a mucous easily removable plaque were noted on hyperemic and hypertrophied tonsils (51.7%). Pathogens was isolated in 58/48.3% of cases, Staphylococcus aureus was isolated in 26/21.7% of cases, Streptococcus pyogenes - in 12/10.0% of cases. Also, Candida albicans was isolated in 13/10.8% of cases and in 7/5.8% of cases, a bacterial-fungal association was detected, which shows the role of these pathogens in the development of purulent-inflammatory manifestations in the oropharynx of patients. Positive result of bacteriological examination (n = 58), anemia of varying severity was noted in 17/29.3% of cases, frequent respiratory infections in 18/31.1% of cases, chronic diseases of the ENT organs (chronic tonsillitis, sinusitis, otitis media) in 23/39.6% of cases, in 6/10.3 In % of cases - chronic bronchitis, which was significantly more common compared with patients with a negative result of bacteriological examination.